Work Without Jobs - Boudreau, John (MIT Sloan Management Review, 2021)
Organizations are held back by an obsolescent work operating system that was built for the Second Industrial Revolution, with work defined as "jobs" and workers defined as "job-holding employees." Leaders must adopt and implement a new approach to organizing work that deconstructs jobs into tasks and deploys workers based on their skills, not job descriptions.